2011
DOI: 10.1016/j.jfms.2011.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Composite Fixation of Comminuted Ilial Wing Fractures in Cats: Three Cases

Abstract: This technique provided a quick and highly adaptable means of stabilising this fracture configuration, as well as restoring pelvic symmetry, when limited buttressing support and bone stock were available cranial and ventral to the acetabulum. This method of fixation may have biomechanical advantages over lateral or dorsal plating techniques for this particular type of fracture configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…Ilial fractures in cats result from trauma and represent 50% of feline pelvic fractures . Indications for surgical repair of pelvic fractures include involvement of the weight‐bearing axis, acetabular fractures, presence of neurologic deficits, and excessive pain . Lateral plating is the most common method of repair for ilial fractures in cats .…”
Section: Introductionmentioning
confidence: 99%
“…Ilial fractures in cats result from trauma and represent 50% of feline pelvic fractures . Indications for surgical repair of pelvic fractures include involvement of the weight‐bearing axis, acetabular fractures, presence of neurologic deficits, and excessive pain . Lateral plating is the most common method of repair for ilial fractures in cats .…”
Section: Introductionmentioning
confidence: 99%
“…It is usual to find out combinations of these fractures with the presence of multiple fragments. Conservative treatment increases the probability of poor bone union and pelvic canal stenosis (BURTON, 2011). This pelvic anatomical deformity leads to complications, such as dystocia, constipation and obstipation, which can lead to the formation of megacolon (MEESON & COO, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The prolonged retention of feces in the colon leads to increased water absorption from the fecal mass, which promotes a greater hardening or stool impaction, generating other associated symptoms, as dyschezia, megacolon and tenesmus. In cats, a perianal hernia may develop due to the dyschezia ,megacolon and weakening of the pelvic muscles (BURTON, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These screws are at increased risk for loosening because they have few threads engaged in these thin bones . Most reports of feline pelvic fracture management and complications are based on small case series, on a few feline patients included in canine studies, or on case series of cats that experienced detrimental pelvic canal collapse after pelvic fracture healing and required some form of pelvic canal widening procedure to address constipation and/or obstipation . A recent case series reported that, of 21 cats with laterally plated iliac fractures, 62% (13/21) had radiographically measurable screw loosening with a mean 13% (range, 0–46%) loss of screw purchase.…”
mentioning
confidence: 99%
“…Additional techniques for pelvic fracture stabilization include screws inserted in lag fashion and a combination of screws, wire, and polymethylmethacrylate . In a recent case report describing revision of a pelvic fracture malunion and pelvic canal collapse with constipation, a 2‐mm‐diameter Steinman pin was placed in an intramedullary (IM) position in the ilium.…”
mentioning
confidence: 99%